Control of visceral leishmaniasis in latin america-a systematic review. - Gustavo A S Romero; Marleen Boelaert (PLoS Neglected Tropical Diseases)
Background While three countries in South Asia decided to eliminate anthroponotic visceral leishmaniasis (VL) by 2015, its control in other regions seems fraught with difficulties. Is there a scope for more effective VL control in the Americas where transmission is zoonotic? We reviewed the evidence on VL control strategies in Latin America-diagnosis, treatment, veterinary interventions, vector control-with respect to entomological and clinical outcomes. Methodology/principal findings We searched the electronic databases of MEDLINE, LILACS, and the Cochrane Central Register of Controlled Trials, from 1960 to November 2008 and references of selected articles. Intervention trials as well as observational studies that evaluated control strategies of VL in the Americas were included. While the use of rapid diagnostic tests for VL diagnosis seems well established, there is a striking lack of evidence from clinical trials for drug therapy and few well designed intervention studies for control of vectors or canine reservoirs. Conclusion Elimination of zoonotic VL in the Americas does not seem a realistic goal at this point given the lack of political commitment, gaps in scientific knowledge, and the weakness of case management and surveillance systems. Research priorities and current strategies should be reviewed with the aim of achieving better VL control.